Ct-Scan Non Kontras Pada Pasien Batu Saluran Kemih - Haryadi Haryadi; Tantri Dwi Kaniya; Anggunan Anggunan; Diana Uyun (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Urinary stones are a disease where hard times are obtained along the urinary tract, urinary stones can be found in the upper urinary system and lower urinary tract, which can cause pain, blockage of the urinary tract and can cause bleeding. Purpose: To determine the results and characteristics of CT SCAN images in patients with urinary tract stones without using contrast in Abdul Moeloek Hospital in Bandar Lampung in 2018-2019. Method: this type of research is a retrospective descriptive research design using a cross-sectional study by taking secondary data. Results: From 40 research samples showing urinary tract stones in women, 19 patients (47.5%), in men 21 patients (52.5%), for the highest age, namely in the early elderly (46-55 years) ) as many as 17 patients and the lowest age group, namely the age of toddlers (0-5 years) 1 patient (2.5%), while for the location is in the Kidney that is 24 (60%), found in the ureter 22 (55%), and in the bladder was found 1 (2.5%). Conclusion: Based on the results of CT-Scan without contrast in patients with urinary tract stones the highest incidence of urinary stones in men and the age group 46-55 years with the most frequent location in the kidney area